A Common Market for film: British policy and the unification of European film. Issue 1 (2nd January 2022) - Stubbs, Jonathan
ABSTRACT: This article examines the formulation and impact of British film policy concerning the unification of European film industries from the immediate post-war era to the end of the 1970s. It focuses on the activities of the Board of Trade, which was instrumental in determining British policy responses to integrationist film movements in Europe as well as the broader process of European unification. Various schemes to pool filmmaking resources and remove trade barriers emerged on the continent, both within and outside the EEC. Some depended on intergovernmental cooperation while others called for the creation of supranational bodies, which would govern film production and trade. Concurrently, the proliferation of film co-production treaties bound the major filmmaking nations of Europe into close practices of cooperation. As this article shows, the UK government stood at the margins of Europe's intergovernmental film diplomacy, assuming a defensive, protectionist position which reflected British resistance to supranational governance.